COMPARISON URINE NEUTROPHIL GELATINASE – ASSOCIATED LIPOCALIN WITH STANDARD PARAMETERS IN MONITORING ACTIVITY LUPUS NEPHRITIS - CLASS IV - Rabrenović, Dr sc. med. Violeta; Petrović, Milica; Rabrenović, Milorad (Journal of Medical Biochemistry, 2022)
Introduction: Lupus nephritis (LN) is one of the most serious complications in the development of systemic lupus erythematosus, that can adversely affect the course and prognosis of this autoimmune disease. Therefore, monitoring the effect of applied therapy, achieving remission, or monitoring LN activity is still a great challenge for nephrologists. This study aimed to compare the urinary neutrophile gelatinase associated lipocalin (u/NGAL) with traditionally accepted parameters for LN activity to indicate the importance of its determination in these patients. Methods: The study group consisted of 40 patients, who were prospectively followed for a period of 4 months within three control visits to 2 months. The first group (20/40) had active LN (Group A), and the second group had LN in remission (Group B). The parameters were compared: proteins/s, albumins/s, C3, C4, anti-ds-DNA Ab, proteinuria 24h, ur.protein / creatinine ratio - Up / cre, u/NGAL (immunochemical method CMIA),GFR. Results: Comparing standard parameters of disease activity and NGAL/u between groups, a statistically significant difference was obtained (p <0.001). Within Group A, comparing the parameters (X ± SD) by visits (0 : 2) for anti-ds-DNA Ab a significance of p <0.05 was obtained, for albumin / s and C3 a significance of p <0.01 was obtained, and proteinuria / 24h, Upr / Cre, u/NGAL had a significance of p <0.001. The negative correlation of u/NGAL was statistically significant at initial visit with albumin/s (p <0.01) as well as the positive correlation with proteinuria 24h and Up / cre (p <0.001). In visit 2 significant negative correlation of u/NGAL with albumin /s and C3 p <0.05, and positive correlation with anti-ds-DNA Ab, proteinuria 24h and Up/cre p <0.001. Conclusion: In our study, the biomarker u/NGAL, showed a statistically significant correlation with traditional parameters of lupus nephritis activity, and its determination could be significant in monitoring LN activity and monitoring responses to applied treatment.